(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Chlorhexidine (CHX) is a widely used antiseptic with broad-spectrum antibacterial activity, but its clinical application in treating bacterial infections like Streptococcus pneumoniae is limited by rapid drug clearance and potential toxicity at high doses. To address these limitations, we developed chlorhexidine-loaded Eudragit nanoparticles (CHX-Eudragit NPs) to enhance the antibacterial efficacy through controlled release and targeted delivery. Eudragit, a biocompatible polymer, was used to encapsulate CHX, forming nanoparticles with an average size of 150 nm and a high encapsulation efficiency. The antibacterial properties of CHX-Eudragit NPs were evaluated against S. pneumoniae using in vitro assays, including minimum inhibitory concentration (MIC), time-kill kinetics, and zone of inhibition tests. Results demonstrated that CHX-Eudragit NPs exhibited superior antibacterial activity compared to free CHX, with a 50% lower MIC value and a larger zone of inhibition. The nanoparticles also displayed a sustained release profile over 72 hours, enabling prolonged antibacterial action. Furthermore, the time-kill assay showed that CHX-Eudragit NPs achieved complete bacterial eradication within 8 hours, significantly faster than free CHX. This study highlights the potential of CHX-loaded Eudragit nanoparticles as a novel and effective strategy for combating Streptococcus pneumoniae infections, particularly in scenarios where prolonged drug release and enhanced antibacterial efficacy are required. These findings suggest that nanoparticle-based delivery systems may offer a promising alternative to conventional antibiotic therapies, addressing issues related to drug resistance and systemic toxicity.